Coping with life: a typology of personal reflexivity - Caetano, A. (The Sociological Quarterly, 2017)
Personal reflexivity is understood as a social competence that makes life in society possible. All individuals reflect upon themselves, taking their social circumstances into consideration, though they do not necessarily do it in the same way. The formation, exercise, and causal efficacy of reflexivity depend on the social processes and contexts involved. This article focuses precisely on the differential component of the exercise of reflexivity. A typology of reflexivity profiles, consisting of five categories, is presented and discussed: self-referential, pragmatic, functional, resistant, and resilient. This typological analysis is the result of sociological research centered on the social mechanisms of personal reflexivity. By means of biographical interviews, the goal was to understand how people think about themselves, what meanings they ascribe to their past choices, how they interpret their present situation, and what future projections they create according to their social circumstances, contexts, and relationships.